Penerapana Ajaran Tamansiswa pada SD Negeri 02 Ngandong Implementation of Tamansiswa Teachings at State Elementary School 02 Ngandong - Saryanto, Saryanto (Jurnal Pengabdian Masyarakat: Pemberdayaan, Inovasi dan Perubahan, 2024)
Tamansiswa teachings, formulated by Ki Hadjar Dewantara, have a main principle known as "Ing Ngarso Sung Tulodho, Ing Madyo Mangun Karso, Tut Wuri Handayani." This principle reflects a holistic approach in education that emphasizes the role of educators as role models, motivators, and supporters for students. The application of this teaching in the context of modern education, especially in Indonesian schools. This study uses a qualitative approach with a case study method in several schools that apply the Tamansiswa principle. The results of the study show that the application of the principle of "Ing Ngarso Sung Tulodho" emphasizes the importance of educators being good examples for students in attitudes, behaviors, and values. The principle of "Ing Madyo Mangun Karso" shows the role of educators in building enthusiasm and motivation to learn among students through inspiring and constructive interactions. Meanwhile, "Tut WuriHandayani" describes the role of educators in providing encouragement and support from behind, allowing students to develop. The implementation of this teaching has proven effective in shaping student character, increasing learning motivation, and creating an inclusive and competitive educational environment. This article concludes that the principles of Tamansiswa are relevant and can be applied in the context of contemporary education to create a more humane and student-centered education system.ABSTRAKAjaran Tamansiswa, yang dirumuskan oleh Ki Hadjar Dewantara, memiliki prinsip utama yang dikenal dengan istilah "Ing Ngarso Sung Tulodho, Ing Madyo Mangun Karso, Tut Wuri Handayani." Prinsip ini mencerminkan pendekatan holistik dalam pendidikan yang menekankan peran pendidik sebagai teladan, pendorong, dan pendukung bagi para siswa. Penerapan ajaran ini dalam konteks pendidikan modern, khususnya di sekolah-sekolah Indonesia. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kasus di beberapa sekolah yang menerapkan prinsip Tamansiswa. Hasil penelitian menunjukkan bahwa penerapan prinsip "Ing Ngarso Sung Tulodho" menekankan pentingnya pendidik menjadi contoh yang baik bagi siswa dalam sikap, perilaku, dan nilai-nilai. Prinsip "Ing Madyo Mangun Karso" menunjukkan peran pendidik dalam membangun semangat dan motivasi belajar di antara siswa melalui interaksi yang inspiratif dan konstruktif. Sementara itu, "Tut Wuri Handayani" menggambarkan peran pendidik dalam memberikan dorongan dan dukungan dari belakang, memungkinkan siswa untuk berkembang Implementasi ajaran ini terbukti efektif dalam membentuk karakter siswa, meningkatkan motivasi belajar, dan menciptakan lingkungan pendidikan yang inklusif dan berdaya saing. Artikel ini menyimpulkan bahwa prinsip-prinsip Tamansiswa relevan dan dapat diterapkan dalam konteks pendidikan kontemporer untuk menciptakan sistem pendidikan yang lebih manusiawi dan berpusat pada siswa.